Tooth bleaching with hydrogen peroxide and nano‐hydroxyapatite: a 9‐month follow‐up randomized clinical trial. Issue 4 (20th January 2015) - Vano, M; Derchi, G; Barone, A; Genovesi, A; Covani, U
Abstract Objectives The aim of this study was to compare the amount of tooth colour change, rebound rate and tooth sensitivity in patients submitted to a bleaching technique with 6% hydrogen peroxide (HP) with or without 2% nano‐hydroxyapatite (n‐HA). Methods Sixty subjects were included in this examiner‐blinded, randomized clinical trial using a 6% HP gel with or without 2% n‐HA. Tooth colour and tooth sensitivity were analysed before and after treatment. All data were analysed statistically. Results After bleaching, both treatments demonstrated significant improvements in tooth shade (P < 0.05 for both groups). At the 9‐month recall, tooth shade remained significantly lighter than at baseline (P < 0.05 for both groups). However, a relapse of the tooth shade was observed compared with the immediate post‐bleaching result (P < 0.05). 6% HP with 2% n‐HA produced significantly lower sensitivity (P < 0.05) than the bleaching product without n‐HA. Colour change evaluation resulted in no difference between the two groups. Conclusion Both treatments demonstrated significant improvements in tooth shade. The bleaching effectiveness of the tested products was comparable. The use of 6% HP with 2% n‐HA reduced the incidence of sensitivity during the bleaching treatment compared to a bleaching agent that did not contain n‐HA.